The Biosynthesis of Enzymatically Oxidized Lipids - William Griffiths (Frontiers in Endocrinology, 2020)
Enzymatically oxidized lipids are a specific group of biomolecules that function as keysignaling mediators and hormones, regulating various cellular and physiological processesfrom metabolism and cell death to inflammation and the immune response. They arebroadly categorized as either polyunsaturated fatty acid (PUFA) containing (free acidoxygenated PUFA “oxylipins”, endocannabinoids, oxidized phospholipids) or cholesterolderivatives (oxysterols, steroid hormones, and bile acids). Their biosynthesis isaccomplished by families of enzymes that include lipoxygenases (LOX),cyclooxygenases (COX), cytochrome P450s (CYP), and aldo-keto reductases (AKR). Incontrast, non-enzymatically oxidized lipids are produced by uncontrolled oxidation andare broadly considered to be harmful. Here, we provide an overview of the biochemistryand enzymology of LOXs, COXs, CYPs, and AKRs in humans. Next, we presentbiosynthetic pathways for oxylipins, oxidized phospholipids, oxysterols, bile acids andsteroid hormones. Last, we address gaps in knowledge and suggest directions forfuture work.